Towards Sustainable Saudi Housing: Balancing Modernity with Traditional Architectural Practices (Future Cities and Environment, 2025)
This paper investigates the impact of integrating traditional and modern architectural practices to enhance energy efficiency and cultural compatibility in Saudi residential buildings. A comparative analysis was conducted between contemporary detached houses and traditional courtyard houses in the Eastern Province of Saudi Arabia. A representative modern house was selected and evaluated using data from architectural consultants. This study highlights the high cooling loads in contemporary designs, which amount to 37,166,250 watt-hours annually, with peak loads in July and August. The reliance on air conditioning is driven by the design's failure to incorporate effective passive cooling strategies. The research proposes modifications to incorporate culturally and climatically effective shading elements. For instance, adding a shading element that allows for cross ventilation while maintaining privacy reduced the cooling load to 29,707,751 watt-hours annually. This represents a reduction of approximately 8 million watt-hours, demonstrating the efficacy of such interventions. The traditional courtyard house design, characterized by its central open courtyard and thick insulative walls, provided superior climatic adaptability, significantly reducing the need for mechanical cooling. These findings suggest that modern Saudi homes can benefit from integrating traditional design elements, such as vertical and bridging shading elements. These strategies not only enhance natural ventilation and thermal comfort but also align with cultural preferences for privacy. This study underscores the importance of revisiting traditional architectural wisdom to address contemporary environmental challenges, advocating for a balanced approach to sustainable housing design in Saudi Arabia.